2019
DOI: 10.2355/isijinternational.isijint-2018-694
|View full text |Cite
|
Sign up to set email alerts
|

Solidification Structure, Non-metallic Inclusions and Hot Ductility of Continuously Cast High Manganese TWIP Steel Slab

Abstract: In the current study, the solidification structure, non-metallic inclusions and hot ductility of continuously cast high manganese TWIP steel slab have been investigated and the inclusion formation behavior have been revealed by FactSage (CRCT-ThermFact Inc., Montréal, Canada). The area ratio of equiaxed grain zone of the TWIP steel slab is 0.18. Two main types of inclusions in the TWIP steel slab are single AlN particle and AlN + MnS aggregates. It is found that MgAl 2 O 4 and AlN particles can precipitate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…In contrast, the subcutaneous microstructure was more coarse than the surface microstructure due to the lower cooling rate. [ 25 ] Therefore, the surface microstructure on the side‐1, which was deformed from subcutaneous was coarse and darker in color, and the microstructure showed a clear streamlined character in the RD direction. The surface microstructure on the side‐2 was less deformed, which was only deformed in the RD direction, with no change in the ND direction.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the subcutaneous microstructure was more coarse than the surface microstructure due to the lower cooling rate. [ 25 ] Therefore, the surface microstructure on the side‐1, which was deformed from subcutaneous was coarse and darker in color, and the microstructure showed a clear streamlined character in the RD direction. The surface microstructure on the side‐2 was less deformed, which was only deformed in the RD direction, with no change in the ND direction.…”
Section: Discussionmentioning
confidence: 99%
“…With the continuous improvement in productivity, more and more attention has been given to the prevention of transverse corner cracks. [6,[8][9][10] There are three brittle temperature zones from the solidification temperature of steel to 600 C. The third brittle temperature zone plays a vital role in controlling the occurrence of angular transverse cracks during continuous casting. In previous studies, it was found that strain rate and deformation temperature have a significant effect on the thermoplasticity of materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] In particular, as fully austenitic high-Mn steels with 12-30 wt% Mn, transformation-induced plasticity (TRIP) and twinning-induced plasticity (TWIP) steels have attracted intense attention due to their remarkable mechanical properties, including high strength, excellent ductility, and high energy absorption capacity, and are promising candidate for the fourth-generation automotive steels. [5][6][7] Therefore, most studies of high-Mn steels have focused on their mechanical properties such as solidification structures, [8,9] nonmetallic inclusions, [10][11][12] tensile ductility [13,14] and deformation behavior, [15,16] etc., whereas studies of the smelting process have been rarely reported.…”
Section: Introductionmentioning
confidence: 99%